log(x+3)(x+5) base 3=1
(x+3)(x+5)=3
x^2+8x+15=3
x^2+8x+12=0
(x+6)(x+2)=0
x=-2 or -6
2006-12-07 03:51:08
·
answer #1
·
answered by raj 7
·
0⤊
0⤋
log3 (x+3)(x+5) = 1
(x+3)(x+5) = 3^1
x² + 8x + 15 = 3
x² + 8x + 12 = 0
(x + 2)(x + 6) = 0
x = -2 or x = -6
But -6 would cause a problem in the original equation, so x=-2.
Everyone seems to forget that you have to make sure that the equation still works by plugging the values back in.
You can't take the ln of a negative number, so any value of x that results in taking the ln of a negative number has to be thrown out.
2006-12-07 03:51:57
·
answer #2
·
answered by Jim Burnell 6
·
0⤊
0⤋
Log3 ((x+3)(x+5))=1
log3 ( x^2+8x+15)=1
3^1=x^2+8x+15
x^2+8x+12=0
(x+2)(x+6)=0
x=-2,-6
2006-12-07 03:52:58
·
answer #3
·
answered by math_teacher_02 2
·
0⤊
0⤋
One property of logarithms is log(y)+log(x) =log(x*y).
So log3(x+3)+log3(x+5)=log3((x+3)*(x+5))=log3(x^2+8x+15)
So log3(x^2+8x+15)=1. Exponentiate both sides by three. Then
3^(log3(x^2+8x+15))=3^1
so
(x^2+8x+15)=3
x^2+8x+12=0
This is a quadratic equation and you can find the roots using the formula. r=(-b±sqrt(b^2-4ac))/(2a)
2006-12-07 03:55:01
·
answer #4
·
answered by thierryinho 2
·
0⤊
0⤋
log3 (x) + log 3(3) + log3 (x) + log 3(5)=1
Take inverse log of both sides
3*10^x + 3*10^3+ 3*10^x + 3*10^5= 10^1
3(10^x+10^x) + 3000+ 300000= 10
20^x= 100996
ln (20^x)= ln 100996
x ln 20= 11.52
x= 11.52/ (ln20)
x=3.84
2006-12-07 03:59:27
·
answer #5
·
answered by ۞ JønaŦhan ۞ 7
·
0⤊
0⤋
im solving it now...have to look at you own formulae to understand...
log3(x+3) + log3(x+5)=1
log(x+3)/log3 + log(x+5)/log3=log0............since log0=1
log(3+3-3) + log(x+5-3) = log0
logx + log(x+2) = log0
log(x*(x+2))=log0
x*x + 2*x = 0...............taking antilog on both sides
x=-2
so, IMO, x= -2
To avoid confusions in quadratic equations when you have to check if you're still getting the answer, simply try to remove/avoid it, by adopting the above method.
2006-12-07 03:58:40
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
log(x+3)(x+5) base 3=1
(x+3)(x+5)=3
x^2+8x+15=3
x^2+8x+12=0
(x+6)(x+2)=0
x=-2 or -6
2006-12-07 03:53:58
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
if the base is 3 then
x^2+8x+12=0
find the roots.
2006-12-07 04:04:42
·
answer #8
·
answered by iyiogrenci 6
·
0⤊
0⤋
-3 and -6
i tink
2006-12-07 03:53:10
·
answer #9
·
answered by silverdragon_1441 1
·
0⤊
0⤋